The Effect of Capital Assistance and Business Assistance on The Empowerment of Mustahik Zakat MSMEs DT Peduli North Sumatra - Indah Khuzaimah; Ahmad Syakir; Budi Harianto (Jurnal Manajemen Bisnis, 2024)
This study aims to determine the effect of capital assistance, and business assistance on increasing the empowerment of mustahik zakat Micro,Small,and Medium Enterprises (MSME). The method used in this research is quantitative research method with data collection techniques using primary data obtained from questionnaires with a Likert scale. Sampling in this study using non probability sampling technique (saturated sample) where the entire population is relatively small in this study to be the entire sample with a total of 30 samples. This research analysis technique uses multiple regression analysis with validity and reliability tests, classical assumption tests, multiple linear regression tests and hypothesis testing with SPSS. The results in this study indicate that partially capital assistance and business assistance have a positive and significant effect on increasing the empowerment of mustahik MSME. Then, capital assistance and business assistance simultaneously have a positive and significant effect on the empowerment of mustahik MSMEs. The X1 and X2 variables affect the Y variable by 63.8%, while the remaining 36.2% is influenced by other variables outside of this study.